A concise guide to writing a thesis or dissertation : educational research and beyond - Kornuta, Halyna M. (Halyna Maria) (Routledge, 2019)
"A Concise Guide to Writing a Thesis or Dissertation provides clear, concise, and intentional practice guidelines about organizing and writing a thesis or dissertation. Part I provides an overview for writing a thesis or dissertation. It describes the big picture of planning and formatting a research study, from identifying a topic through to writing quality. Part II describes the framework and substance of a research study. It models the pattern generally found in a formal, five-chapter research study"--